High-speed demonstration of a superconducting pseudo-random bit-sequence generator. - Wang, Z.
This paper describes the design, analysis and test results for a 4-bit pseudo-random bit-sequence generator (PRBSG) implemented with complementary output switching logic (COSL) gates. The PRBSG was optimized using a Monte Carlo simulation method for 10-GHz operation. The circuit has been fabricated using niobium technology with critical current density of 1 kA/cm2 and sheet resistance of 1 Ω/sq. The 4-bit PRBSG consists of 12 gates and its area is 1530×950 μm2. It has been fully tested with a three-phase power supply, and its power consumption is 0.15 mW. The correct operations have been verified experimentally at clock frequencies of up to 2 GHz
Keywords: 0.15 W; 2 to 10 GHz; 4 bit; Monte Carlo simulation; Nb; Complementary output switching logic gate; Critical current density; High-speed circuit; Niobium technology; Sheet resistance; Superconducting pseudo-random bit-sequence generator